Risk factors for cutaneous leishmaniasis in a high-altitude forest region of Peru - Justin T. Lana; Andrés Mallipudi; Ernesto Ortiz; Heriberto Arévalo Ramírez; Alejandro Llanos‐Cuentas; William Pan (My University, 2021)
BACKGROUND: American cutaneous leishmaniasis (CL) is a neglected tropical disease typically associated with men working in remote, sylvatic environments. We sought to identify CL risk factors in a highly deforested region where anecdotal reports suggested an atypical proportion of women and children were infected with CL raising concern among authorities that transmission was shifting towards domestic spaces and population centers. METHODS: We describe the characteristics of CL patients from four participating clinics after digitizing up to 10 years of patient data from each clinic's CL registries. We assessed risk factors of CL associated with intradomestic, peridomestic, or non-domestic transmission through a matched case-control study with 63 patients who had visited these same clinics for CL (cases) or other medical reasons (controls) between January 2014 and August 2016. The study consisted of an in-home interview of participants by a trained field worker using a standard questionnaire. Risk factors were identified using bivariable and multivariable conditional logistic regression. RESULTS: Between 2007 and 2016, a total of 529 confirmed CL positives were recorded in the available CL registries. Children and working aged women made up 58.6% of the cases. Our final model suggests that the odds of sleeping in or very near an agricultural field were five times greater in cases than controls (p = 0.025). Survey data indicate that women, children, and men have similar propensities to both visit and sleep in or near agricultural fields. CONCLUSIONS: Women and children may be underappreciated as CL risk groups in agriculturally dependent regions. Despite the age-sex breakdown of clinical CL patients and high rates of deforestation occurring in the study area, transmission is mostly occurring outside of the largest population centers. Curbing transmission in non-domestic spaces may be limited to decreasing exposure to sandflies during the evening, nighttime, and early morning hours. Our paper serves as a cautionary tale for those relying solely on the demographic information obtained from clinic-based data to understand basic epidemiological trends of vector-borne infections.
Keywords: Medicine; Odds ratio; Transmission (telecommunications); Demography; Odds; Population; Logistic regression; Tropical medicine; Risk factor; Environmental health; Pediatrics; Family medicine; Pathology; Sociology; Electrical engineering; Engineering; Internal medicine; Medicine; Odds ratio; Transmission (telecommunications); Demography; Odds; Population; Logistic regression; Tropical medicine; Risk factor; Environmental health; Pediatrics; Family medicine; Pathology; Health Sciences Medicine Public Health, Environmental and Occupational Health Research on Leishmaniasis Studies; Health Sciences Medicine Epidemiology Trypanosoma species research and implications; Physical Sciences Environmental Science Health, Toxicology and Mutagenesis Insects and Parasite Interactions